Intellectuals networks in front of the fascism: cultural and political controversies about the Italian racial laws and exiles in Argentina | Redes intelectuales ante el fascismo: polémicas culturales y políticas acerca de las leyes raciales italianas y los exilios en Argentina - Leticia Prislei (Pasado y Memoria, 2012)
This work sets out to release some of the threads that tile the plot of our political culture using like via of entrance the conflicts and combats that get rid at that time in the world. Multiple indications of the effects caused by the putting in use of the racial laws of the Italian fascism in 1938 and exiles derived from the same ones emerge in publications of the Italian daily press, of Argentine newspapers and the cultural magazines. Their echoes not yet stop. | Este trabajo se propone relevar algunos de los hilos que tejen la trama de nuestra cultura política utilizando como vía de entrada los conflictos y combates que se libran por entonces en el mundo. Múltiples indicios de los efectos provocados por la puesta en vigencia de las leyes raciales del fascismo italiano en 1938 y los exilios derivados de las mismas emergen en publicaciones de la prensa cotidiana italiana, de los diarios argentinos y las revistas culturales. Sus ecos aún no cesan.